The portrayal of the Balkans in the Slovenian translations of Karl May’s Orientzyklus - Trupej, Janko (Annales. Series historia et sociologia, 2024)
This article discusses the depiction of the Balkans in two Slovenian translations of Karl May’s Orientzyklus. This hexalogy was translated for the first time at a time when most of the Slovenian ethnic territory was part of the Kingdom of Yugoslavia, and it was later retranslated when Slovenia was a republic in the Socialist Federal Republic of Yugoslavia. A textual comparison of the originals and translations shows that in the first translations, numerous interventions were made to portray the Balkans in a more negative manner than in the originals, whereas in the retranslations, May’s frequently negative depiction of the region was somewhat mitigated.
Keywords: Balkan; German literature; književno prevajanje; May, Karl; nemška književnost; orientalism; orientalizem; translation